Early decrease in the podocalyxin to synaptopodin ratio in urinary Fabry podocytes - Trimarchi, Hernán (Clin Kidney J, 2018)
BACKGROUND: In Fabry nephropathy, podocyturia is an early event that may lead to glomerulosclerosis and chronic kidney disease. The glycocalyx is a potential podocyte damaged compartment in glomerulopathies. We investigated glycocalyx podocalyxin in urinary detached podocytes compared with cytoplasmic synaptopodin. METHODS: This was a cross-sectional study including 68 individuals: Controls (n = 20) and Fabry patients (n = 48), 15 untreated and 33 treated. Variables included age, gender, urinary protein/creatinine ratio (UPCR), estimated glomerular filtration rate (eGFR), lyso-triasocylsphingosine (lyso-Gb3) levels and enzyme replacement therapy (ERT). Podocyturia was assessed by immunofluorescence and podocyte subpopulations were analyzed. RESULTS: Fabry patients displayed higher podocyturia than controls. Fabry treated subjects (n = 33) presented significantly higher UPCR compared with untreated ones (n = 15); podocyturia, eGFR and lyso-Gb3 levels were not different. All control podocytes colocalized synaptopodin and podocalyxin; 13 Fabry patients (27%) colocalized these proteins, while 35 (73%) were only synaptopodin positive. No podocalyxin-positive/synaptopodin-negative cells were encountered. In Fabry patients, podocyturia was significantly higher and proteinuria lower in those that colocalized. CONCLUSION: Fabry patients present higher podocyturia and a presumably more damaged glycocalyx assessed by podocalyxin. Treated patients had significant higher proteinuria suggesting ERT is initiated late, at advanced stages. The degree of podocalyxin-negative podocytes was similar in both groups, but colocalization was associated with lower proteinuria. Podocyturia assessed by podocalyxin alone may be underestimated. The implications of podocyte glycocalyx damage deserve further investigations.